Association of IL-8 (-251 a/t) gene polymorphism with clinical parameters and chronic periodontitis. - Hengameh Khosropanah; Eskandar Kamali Sarvestani; Ashkan Mahmoodi; Masoud Golshah (Tehran University of Medical Sciences, 2013)
To investigate the correlation between IL-8 (-251 A/T) gene polymorphism and susceptibility to chronic periodontitis as well as different clinical parameters and severity of the condition in patients referred to dental school, Shiraz University of Medical Sciences, Shiraz, Iran.In this randomized cross sectional study, 227 non-smoking patients with chronic periodontitis (test) and 40 healthy individuals (control) were enrolled in this experiment and the following clinical parameters were employed in the study: Periodontal Pocket Depth (PPD), Clinical Attachment Level (CAL) and Bone Loss (BL). All participants underwent the PCR (Polymerase Chain Reaction) test to detect 251 A/T Single Nucleotide Polymorphism of IL8 gene.No significant correlation was perceived between different genotypes of IL-8 and the severity of the periodontal condition (P= 0.164), neither did we detect any substantial association between different IL-8 genotypes and the mean PPD (P=0.525), CAL (P=0.151), BL (P=0.255), PI (P=0.087), BOP (P=0.265) and the average number of teeth (P=0.931).The results implied that there was no explicit correlation between 251 (A/T) IL-8 gene polymorphism and the severity of the chronic periodontal disease or to the susceptibility to it.